2016
DOI: 10.2174/1573403x12666160622102802
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Pharmacotherapy and Supports in the Elderly - A Short Review

Abstract: Heart failure is predominantly a disease of the elderly with an increasing prevalence with increasing age. Increasing age is also associated with increased multi-morbidity such that elderly heart failure patients typically have five to six comorbidities in addition to heart failure. Elderly patients are also more likely to have heart failure with preserved ejection fraction (HFpEF), and there are fewer evidence-based treatments with proven efficacy in HFpEF. Hence the management of heart failure in these patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Particularly, HF prevalence has increased to 6.5 million in Americans ≥20 years of age ( Benjamin et al, 2017 ). Over the last several years, there has been an increase in the incidence and prevalence of HF in the elderly, drastically impacting their survival rate and quality of life ( Shakib and Clark, 2016 ; Ziaeian and Fonarow, 2016 ). HF represents the final common clinical event of numerous cardiovascular diseases (CVDs); coronary artery disease (CAD) followed by myocardial ischemia is the most common cause worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, HF prevalence has increased to 6.5 million in Americans ≥20 years of age ( Benjamin et al, 2017 ). Over the last several years, there has been an increase in the incidence and prevalence of HF in the elderly, drastically impacting their survival rate and quality of life ( Shakib and Clark, 2016 ; Ziaeian and Fonarow, 2016 ). HF represents the final common clinical event of numerous cardiovascular diseases (CVDs); coronary artery disease (CAD) followed by myocardial ischemia is the most common cause worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The present mid-term analysis indicated that slightly more than half the patients had been switched to an oral β-blocker, most commonly bisoprolol/ bisoprolol fumarate (84%), although the mean initial dose of 1.66 mg was at the low end of the bisoprolol dose range risk of mortality has also been reported for HF patients. [25][26][27] This was observed in CHART-2, 28 as well as in JCARE-CARD, which reported an adjusted HR for all-cause mortality of 2.15 (95% CI 1.62-2.86) for age ≥80 vs. <80 years. 29 Mid-term findings of the AF-CHF Landiolol Survey appear to be consistent with these reports.…”
Section: Discussionmentioning
confidence: 72%
“…Patients who are diagnosed with HFpEF are generally older compared with patients with HFrEF [15], and frailty is a common issue experienced by elderly patients with HF [72,73]. Frailty is defined as having low grip strength, low energy, slow walking speed, and low physical activity [72] and has been associated with a 92% and 65% increased likelihood of emergency department visits and hospitalizations [73], respectively, in frail patients with HF compared with those who were not frail. Frailty may be negatively impacted by comorbidities, which can impair patients' ability to care for themselves [72].…”
Section: Normalmentioning
confidence: 99%
“…Frailty is defined as having low grip strength, low energy, slow walking speed, and low physical activity [72] and has been associated with a 92% and 65% increased likelihood of emergency department visits and hospitalizations [73], respectively, in frail patients with HF compared with those who were not frail. Frailty may be negatively impacted by comorbidities, which can impair patients' ability to care for themselves [72]. As such, greater collaboration among PCPs, patients, and their caregivers may facilitate assessment of their quality-of-life (QoL) issues, end-of-life values, preferences in decision-making, management of comorbidities, and provide educational support [71,74].…”
Section: Normalmentioning
confidence: 99%